2005
DOI: 10.1074/jbc.m409066200
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Juxtanuclear Translocation of Protein Kinase C βII by a Negative Feedback Mechanism Involving Ceramide Formed from the Salvage Pathway

Abstract: In a previous study, we showed that protein kinase C ␤II (PKC ␤II) translocated to a novel juxtanuclear compartment as observed in several cell types (Becker, K. P., and Hannun, Y. A. (2003) J. Biol. Chem. 278, 52747-52754). In this study, we noted the absence of this translocation in MCF-7 breast cancer cells, and we examined the mechanisms underlying this selectivity of response. We show that sustained stimulation of PKC ␤II with 4␤-phorbol 12-myristate 13-acetate (PMA) resulted in accumulation of ceramide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 28 publications
3
54
0
Order By: Relevance
“…An increase in sphingosine has been shown to occur in response to TNF-α [61], serum starvation [62], interleukin-1β [63], bradykinin [64], phorbol ester [17], and Fas ligands [65]. The release of sphingosine is presumed to arise from enhanced degradation of complex sphingolipids, sphingomyelin or ceramide.…”
Section: Iii) An Increase In Free Sphingosinementioning
confidence: 99%
See 4 more Smart Citations
“…An increase in sphingosine has been shown to occur in response to TNF-α [61], serum starvation [62], interleukin-1β [63], bradykinin [64], phorbol ester [17], and Fas ligands [65]. The release of sphingosine is presumed to arise from enhanced degradation of complex sphingolipids, sphingomyelin or ceramide.…”
Section: Iii) An Increase In Free Sphingosinementioning
confidence: 99%
“…Recent studies have begun to implicate members of the PKC of Ser/Thr protein kinases as upstream regulators of the sphingoid base salvage pathway resulting in ceramide synthesis following PKC activation in human breast cancer cell line (MCF-7 cells) [17,23].Initially, it was shown that PKC activation by phorbol esters stimulated the formation of ceramide, and it was concluded that phorbol esters activated the de novo pathway [4], based on the sensitivity of ceramide formation to fumonisin B1. However, in a more recent study, it was shown that phorbol ester-induced ceramide was not myriocin-sensitive.…”
Section: Regulation Of the Salvage Pathway 4-1 The Salvage Pathway Amentioning
confidence: 99%
See 3 more Smart Citations